THE EFFECT OF AUTOGENIC RELAXATION TECHNIQUES ON ANXIETY LEVELS IN TRIMESTER III PREGNANT WOMEN IN THE WORK AREA OF KEMBANG MUMPO HEALTH CENTER - sari, ruri maiseptya (Poltekkes Kemenkes Medan, 2021)
Anxiety is a feeling of not relaxing because of fear that is accompanied by a response. Treatment of anxiety that occurs in primigravida mothers can be done with non-pharmacological therapy, one of which is autogenic relaxation. The research objective was to study the effect of autogenic relaxation techniques on anxiety levels in third trimester mothers in the working area of ??the Kembang Mumpo Health Center. This type of research is pre-experimental, with a one group pre-test and post test design. The population in this study were 21 third trimester pregnant women at the end of the June-July period who experienced anxiety. Sampling in the study with a Purposive sampling technique, namely 10 people. The analysis technique used is the T-test statistical test. The results of the univariate analysis showed that the average anxiety level of third trimester pregnant women before autogenic relaxation techniques was performed was 24.7. The average level of anxiety of third trimester pregnant women after autogenic relaxation techniques was 18.8. The results of the bivariate analysis obtained the value of ?Value = 0.000 <? (0.05). It was concluded that there was an effect of autogenic relaxation techniques on the anxiety level of third trimester pregnant women in the Kembang Mumpo Health Center Work Area. The results of this study are expected to incorporate autogenic relaxation techniques into the health workers' monthly activity agenda for handling anxiety in pregnant women. Especially for midwives, it is hoped that they will be able to equip themselves with various safe methods, namely relaxation. One of them is autogenic relaxation which is useful for helping midwives in overcoming client problems, especially pregnant women with anxiety.